Effect of electric current on fracture and constitutive behavior of SN-Ag-Cu solder joints. (15th February 2017) - Yao, Yao; An, Ru; Long, Xu
Highlights: The current density effect to solder failure has been investigated experimentally and theoretically. A constitutive model for solder under electricity has been developed. Unified creep plasticity and damage evolution are included in the proposed model. The simulation results show good agreement compared with experimental data. Abstract: The effect of electric current density on the tensile fracture property of 96.5SN-3.0Ag-0.5Cu (in wt.%) solder joints was studied. Experimental results indicate that the mechanical property was profoundly affected by the electric current due to electromigration. The variation of ductility, plasticity and rupture strain was revealed by the stress-strain curves obtained from experimental studies. Based on the mechanism of elastic-plasticity and damage, a unified creep-plastic-damage constitutive model with variables of plastic strain, damage threshold and inelastic dissipation was developed. The relationship of damage parameters and electric current time has been determined from experimental and numerical analysis. In general, the proposed model can predict mechanical behaviors of solder under current density with reasonable accuracy.